Mechanical characterization of PM aluminum composites by small punch test - Moreno,Mario Fredy (2018)
ABSTRACT In this work Small Punch Test (SPT) was applied to study the mechanical behavior of ultrafine-grained Al-Al2O3metal matrix composites (MMCs) fabricated in situ via powder metallurgy route (HITEMAL®). Such MMCs show attractive mechanical properties, enhanced creep performance and increased thermal stability at elevated temperatures, not normally associated with service of conventional Al alloys, even after prolonged high temperature exposure. MMCs fabricated from two powders of different particle size (d50 = 8.9 and 1.2µm) were evaluated in the present work. SPT was performed at room temperature using disc-shaped specimens of 10 mm in diameter. The effect of the different disc thickness (0.4, 0.5 and 0.6 mm) on the load vs. displacement function was evaluated. The displacements monitored from top and bottom sites of the specimen varied during the course of the test. The discs deformed throughout the test by two plastic stages, typical for ductile materials. The relation between load-displacement and stress–strain tensile curves for both composites was analyzed. A drastic change of mechanical behavior between the green compact of cold pressed material and the hot forged material was detected. New methods of determination of a characteristic load PY, which represents a transition from elastic to plastic bending regime were presented and discussed. A relationship between PY and corresponding yield stress was studied for each composite material by a calculation of their respective correlation parameters.